Lexical Error Analysis of Indonesian-English Translation of Texts in Dewantara Kirti Griya Museum - Ahimsa W. Swadeshi; Adi Sutrisno (Lexicon, 2021)
The current research aims to examine lexical errors in Indonesian-English translated texts in Museum Dewantara Kirti Griya. The classification of Lexical Errors proposed by Legenhausen (1975, as cited in James, 2013) is applied in analysing the texts. From 43 texts, the result indicates that there are 88 errors, classified into formal errors (62,5%) and semantic errors (37,5%). The first one deals with the arrangement of words and phrases, while the second deals with meaning and collocation. The most common errors are about the confusion between concepts and terms. This happens when the translator meets local-cultural terms in the SL that needs extra effort to translate.